Controlled growth of SnSe/MoS2 vertical p–n heterojunction for optoelectronic applications. Issue 1 (18th January 2021) - Wang, Xingwang; Zheng, Biyuan; Yi, Jiali; Liu, Huawei; Sun, Xingxia; Zhu, Chenguang; Liu, Ying; Fang, Lizhen; Li, Dong; Pan, Anlian
Abstract: Two-dimensional (2D) heterostructures have been widely studied in recent years and are envisioned to play a key role in future integrated electronics and optoelectronics. The thus-involved van der Waals integration technique provides a feasible way to integrate different 2D materials even with diverse crystal structures into heterostructures, providing a promising platform to explore new artificial materials with new properties. Here, for the first time, we have successfully realized the combination of orthogonal selenide (SnSe) with hexagonal MoS2 into p–n heterojunctions though a two-step chemical vapor deposition method. High resolution transmission electron microscopy characterization shows that multilayer SnSe nanosheet is vertically stacked on MoS2 nanosheet with high crystallinity. The precise spatial modulation of SnSe/MoS2 heterostructures is verified by Raman diagrams. At the same time, the electrical and optoelectronic properties are probed though designing SnSe/MoS2 p–n junction devices. Typical current rectification behaviors are obviously observed in dark condition. While under light illumination, obvious photovoltaic behavior is observed. Maximum short-circuit current ( I sc ) and photon-electron conversion efﬁciency ( η ) are measured to be 67 nA and 1.8%, respectively. The results also indicate that the heterostructure can be employed for reliable ultra-sensitive photodetection, where maximum photoresponsivity is measured to be 384 A W −1 . The direct vapor growth of 2D p–n junctions with different lattice symmetries may expand the platform for the realization of new 2D electronic and optoelectronic devices.